Feminist tennis games between reality and challenges 2020 - Mahmoud Jassim, Ghada (International Journal of Psychosocial Rehabilitation, 2020)
After the researcher conducted a survey of research in the field of tennis games in a number of different aspects, she did not find a study similar to the idea of the research, in addition to the personal interviews that she conducted with some of the professors and trainers for this activity and asked the question that was going on what are the most important reasons that led to the low level Women sports in tennis games in Iraq, so the answers differed between a coach or a specialist and another to him. The researcher inquires through this study. Therefore, the researcher intended to identify and identify the most important reasons that led to the low level of female sport in tennis games, and the researcher assumed that there are statistically significant differences for the most important reasons that led to the low level of female sport in tennis games.